Aerosol-induced brucellosis increases TLR-2 expression and increased complexity in the microanatomy of astroglia in rhesus macaques - Lee, Kim M.; Chiu, Kevin B.; Sansing, Hope A.; Didier, Peter J.; Ficht, Thomas A.; Arenas-Gamboa, Angela M.; Roy, Chad J.; MacLean, Andrew G. (Frontiers in Cellular and Infection Microbiology, 2013)
Brucella melitensis, a bacterial pathogen and agent of epizootic abortion causes multiple pathologies in humans as well as a number of agriculturally important animal species. Clinical human brucellosis manifests as a nonspecific, chronic debilitating disease characterized by undulant fever, arthropathies, cardiomyopathies and neurological sequelae. These symptoms can occur acutely for a few weeks or persist for months to years. Within the brain, endothelial and glial cells can be infected leading to downstream activation events including matrix metalloprotease (MMP) and cytokine secretion and Toll-like receptor (TLR) signaling. These events are likely to lead to tissue remodeling, including morphologic changes in neuronal and glial cells, which are linked to neurological complications including depressive behavior, immune activation and memory loss. Our hypothesis was that B. melitensis infection and neurobrucellosis would lead to activation of astrocytes through upregulation of TLR2 and stimulate concurrent changes in the microanatomy. All six animals were infected via inhalation route. TLR2 expression was approximately doubled in white matter astrocytes of infected rhesus macaques. There was also a 50% increase in the number of astrocytes per unit area in subcortical white matter tracts suggesting increased innate immune activation. This coincided with dramatic increases in the length and complexity of the cell arbor of hypertrophic astrocytes in both cortical grey and white matter. Thus, aerosol-induced brucellosis results in dramatically increased innate immune activation of astrocytes in the absence of widespread neuroinflammation.